Tinjauan Hukum Islam Terhadap Pernikahan Beda Kasta (Studi Kasus Desa Ngafan Kabupaten Maluku Tenggara): Islamic Law View of Different Caste Marriages (Case Study of Ngafan Village Southeast Maluku Regency) - Mahmuddin, Ronny; Saifullah bin Anshor; Ngaja, Hamdan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This study aims to determine the prohibition of inter-caste marriage in Ngafan Village, Southeast Maluku, and Islamic legal views on caste marriage in the customs of the Kei tribe, especially in Ngafan Village, Southeast Maluku Regency. This research is descriptive qualitative research with the type of field research (Field Research). The data collection techniques used were in-depth interviews and documentation. The results showed that: 1) The prohibition of inter-caste marriage (not equal) carried out by some people in Ngafan Village is the prohibition of marriage between women from the Mel-Mel caste (highest caste) and men from Riy-Riy (lowest caste). If there is a marriage between these castes, it depends on their family, if they agree then the marriage is still safe, but if they refuse the marriage can be canceled. 2) In Islamic law the scholars differ on the issue of caste (equality) in marriage. Jumhur ulama said that the caste referred to in marriage is religion, independence, social strata and, descent. Imam Malik said that the caste in question was the religion and was free from diseases that were deemed incurable. Meanwhile, the al-Ẓahiriyyah mazhab said that only Muslims were the conditions for marriage. The scholars do not require that caste be part of the legal requirements of marriage, but caste is included in the category of luzu> m requirements, a condition that allows a female guardian to request an annulment of marriage if the male partner is not in the same caste. So the prohibition of marriage is not equal in Ngafan Village can be justified based on the opinion of some scholars. The implementation of this research is expected to contribute theoretically and practically to religious leaders, parties with special interests, and society in general.